Electrochemical characterization of graphene nanocomposites for development of robust biosensor - Arris, Farrah Aida; Ahmad, Siti Khadijah; Wan Salim, Wan Wardatul Amani (2015)
In this study, reduced graphene oxide (rGO) conjugated with gold nanoparticles (AuNPs) in cellulose-nanofiber (CN) matrices, denoted as rGO-AuNP/CN nanocomposite, was characterized via electrochemical methods. The nanocomposite functions as a transducer layer for a flexible and environmentally friendly flexible glucose sensor. The rGO-AuNPs/CN nanocomposite transducer layer was fabricated via an easy two-step physical and subsequent electrochemical deposition method. Surface morphology of the transducer layer was investigated via scanning electron microscopy (SEM). Fourier transform infrared spectroscopy (FTIR) was used to identify molecule fingerprints of the nanocomposites. Cyclic voltammetry was used to characterize redox capability of the transducer layer. Glucose oxidase (GOx) was subsequently immobilized on the optimized transducer layer for glucose sensing. The best electroactive surface area was determined according to Randles-Sevcik method, where surface current density of 17.3  0.5 μA mM-1 cm-2 was achieved. The optimized rGO-AuNP/CN-TMOS-GOx exhibits amperometric sensitivity of 1350  15.5 nA mM-1, selectivity of 8.1% and 9.9% over 1mM glucose solution for ascorbic acid and acetaminophen respectively, with a detection limit as low as 2.9 μM. The glucose sensor also shows a good linear response range of 0.0032 to 15 mM and good stability with only a 25% loss of enzyme activity after 30 days. All experiments were performed at ambient temperature in the range of 29 to 32oC.